2018
DOI: 10.20884/1.jks.2018.13.3.813
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Listening Mozart Music With Murotal Al Quran on the Pain of Hypertension Patients

Abstract: <p><strong>Absstract</strong></p><p><em><strong>The number of people with hypertension is increasing over time. The most frequest complaint experienced by people with hypertension is pain. Complications of pain can be avoided through correct pain management. Listening to music and murotal Al Quran on some researches can provide a relaxation effect that potentially reduces pain. This study was aimed to identify differences effect in listening mozart music with murotal A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 2 publications
1
6
1
2
Order By: Relevance
“…Listening to murotal surah Ar Rahman can be recommended as a complementary therapy option and non pharmacology in reducing pain of patients with hypertension. [10] This current research is in line with the study conducted by Haryanto, et al (2014), which compared the difference of classical music therapy against the Qur'an murottal therapy on elderly hypertension patients in House of Tresna Wherdha Mulya Darma Pontianak. Shortly, those study showed that there was difference among classical music therapy and Qur'an murottal therapy in dropping blood pressure.…”
Section: B Bivariat Analysissupporting
confidence: 87%
“…Listening to murotal surah Ar Rahman can be recommended as a complementary therapy option and non pharmacology in reducing pain of patients with hypertension. [10] This current research is in line with the study conducted by Haryanto, et al (2014), which compared the difference of classical music therapy against the Qur'an murottal therapy on elderly hypertension patients in House of Tresna Wherdha Mulya Darma Pontianak. Shortly, those study showed that there was difference among classical music therapy and Qur'an murottal therapy in dropping blood pressure.…”
Section: B Bivariat Analysissupporting
confidence: 87%
“…DOI The contributing factor from this study is a kind of slow tempo musical therapy. The tempo of murotal Al quran with qari Muzzamil Hasbalah is 95,99 [15]. Music with slow tempo produces a relaxation effect for listener.…”
Section: Discussionmentioning
confidence: 99%
“…The murottal used in this study had a tempo of 95.99 per minute. The same recording of murottal has also been used in research by [7] to identify the therapeutic approaches effect on pain sufferers of hypertension. Murottal physically contains a human sound element that has a remarkable therapeutic effect.…”
Section: Methodsmentioning
confidence: 99%